An ultra‐rigid close‐stacked piezo motor for harsh condition scanning probe microscopy. Issue 5 (2nd September 2014) - Guo, Ying; Hou, Yubin; Lu, Qingyou
Summary We designed and produced a nearly closest packed stack motor with only one tiny gap of 0.15 mm in the middle of the stack. A low‐voltage method of controlling the motor is introduced for the first time. Besides, the test results of the motor and the corresponding scanning tunneling microscope are also presented. To our surprise, it turns out to be so rigid that even running two oil pumps and one ultrasonic cleaner within 1 m range from a STM directly driven by this new motor cannot cause the STM to produce any visible difference in its the atomic resolution quality. This is a leap in building a true harsh condition atomic resolution SPM. SCANNING 36:554–559, 2014. © 2014 Wiley Periodicals, Inc.